2023
DOI: 10.3390/polym15173531
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of the Mechanical Properties and Mix Proportion of Multiscale-Fibre-Reinforced Engineered Cementitious Composites

Bowei Yang,
Chen Wang,
Song Chen
et al.

Abstract: Engineered cementitious composites (ECCs) are cement-based composite materials with strain-hardening and multiple-cracking characteristics. ECCs have multiscale defects, including nanoscale hydrated silicate gels, micron-scale capillary pores, and millimetre-scale cracks. By using millimetre-scale polyethylene (PE) fibres, microscale calcium carbonate whiskers (CWs), and nanoscale carbon nanotubes (CNTs) as exo-doped fibres, a multiscale enhancement system was formed, and the effects of multiscale fibres on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…They can be used to manufacture various types of materials, such as ion exchange resins, activated carbon, molecular sieves, and components used in fine chemicals, 70 , 71 The adsorption properties, specific surface area, and ionic conductivity of these whiskers can be altered to a certain extent, allowing them to have more functions and applications. 72 Inorganic salt whiskers mainly include CaSO 4, 73–75 CaCO 3 , 76 , 77 magnesium oxide(MgO), 72 , 78 zinc sulfide(ZnS), 79 and TiO₂, 80 , 81 which have a wide range of applications in the industrial field. CaSO 4 whiskers are mainly used for reinforcing and toughening polymer materials such as plastics, rubber, and coatings.…”
Section: Classification Of Whiskersmentioning
confidence: 99%
“…They can be used to manufacture various types of materials, such as ion exchange resins, activated carbon, molecular sieves, and components used in fine chemicals, 70 , 71 The adsorption properties, specific surface area, and ionic conductivity of these whiskers can be altered to a certain extent, allowing them to have more functions and applications. 72 Inorganic salt whiskers mainly include CaSO 4, 73–75 CaCO 3 , 76 , 77 magnesium oxide(MgO), 72 , 78 zinc sulfide(ZnS), 79 and TiO₂, 80 , 81 which have a wide range of applications in the industrial field. CaSO 4 whiskers are mainly used for reinforcing and toughening polymer materials such as plastics, rubber, and coatings.…”
Section: Classification Of Whiskersmentioning
confidence: 99%
“…This includes mixing fibers with varying stiffness, elastic modulus, or scale to enable different fibers to function optimally at different stress stages, thereby enhancing the mechanical properties of the composite materials [28,29]. Yang [30] developed a multiscale reinforcement system using millimeter-level PE fiber, micro-scale calcium carbonate whisker, and nano-scale carbon nanotubes as externally doped fibers. The results indicated that calcium carbonate whisker exerted the greatest influence on compressive strength, while polyethylene fiber had the greatest impact on bending and tensile strength.…”
Section: Introductionmentioning
confidence: 99%